Indian philosophy and yoga in Germany - Ware, Owen (Routledge, 2024)
"This book sheds new light on the fascinating - at times dark and at times hopeful - reception of classical Yoga philosophies in Germany during the nineteenth century. Written for non-specialists, Indian Philosophy and Yoga in Germany will be of interest to students and scholars working on 19th-century philosophy, Indian philosophy, comparative philosophy, Hindu studies, intellectual history, and religious history"--